Impact of COVID-19 pandemic on patterns of cigarette, hookah and marijuana consumption among undergraduate students of University of Sarajevo Bosnia and Herzegovina: a repeated cross-sectional study - Šljivo, A.; Ćetković, A.; Kulo Ćesić, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Aim. The aim of the study was to assess the impact of COVID-19 pandemic on patterns of cigarette, hookah and marijuana consumption among undergraduate students of Bosnia and Herzegovina.Methods. The first part of the double cross-sectional study was conducted among undergraduate students of the University of Sarajevo from 22nd to 26th January 2020, prior to the first COVID-19 case in the country (study period 1), and the second part from March 25th to August 26th 2021, during the third wave of COVID19 outbreak (study period 2). Results. The majority of the 1,230 respondents were women (N1 70.9%, N2 70.1%), pursuing medical sciences (N1 60.0%, N2 55.0%), in their 3rd year of study (N1 26.3%, N2 26.7%), and living in urban environment (N1 84.9%, N2 86.4%). Similar proportion of cigarette smokers (N1 38.5%, N2 39.2%), and smaller, similar portions of hookah smokers (N1 19.3%, N2 21.1%) were classified in both study periods, while the smallest portion of marijuana smokers (N2 8.0%) was classified during COVID-19. Similar number of cigarettes per day, types of cigarettes consumed and consumption frequency in the last 30 days, with the similar independent predictors of cigarette consumption (being woman and living in rural environment associated with decreased risk, and age older than 22 associated with increased risk) were identified both before and during COVID-19 pandemic. Compared to before COVID-19 pandemic, increased trends in intentions (73.6% vs. 81.2%) and attempts (51.9% vs. 75.1%) to smoking cessation among cigarette smokers, but decreased determination not to smoke in the coming year among cigarette non-smokers (N1 72.2%, N2 51.6%) and decreased awareness of smoking harmfulness among both cigarette smokers (N1 68.0%, N2 46.5%) and especially cigarette nonsmokers (N1 60.9%, N2 22.9%) were seen during COVID-19 pandemic. Also, risky behavior among hookah smokers was evident during COVID-19 pandemic. Conclusions. COVID-19 pandemic seemed to positively affect intentions and attempts to smoking cessation among cigarette smokers while negatively affecting attitudes towards cigarette smoking among cigarette non-smokers.